2016
DOI: 10.1088/1674-1056/25/10/106801
|View full text |Cite
|
Sign up to set email alerts
|

Thick c-BN films deposited by radio frequency magnetron sputtering in argon/nitrogen gas mixture with additional hydrogen gas

Abstract: The excellent physical and chemical properties of cubic boron nitride (c-BN) film make it a promising candidate for various industry applications. However, the c-BN film thickness restricts its practical applications in many cases. Thus, it is indispensable to develop an economic, simple and environment-friend way to synthesize high-quality thick, stable c-BN films. High-cubic-content BN films are prepared on silicon (100) substrates by radio frequency (RF) magnetron sputtering from an h-BN target at low subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Figure 1a shows the FTIR spectra obtained from BN films using pure N 2 plasma at 470 • C with different deposition times. The absorption band at 1091 cm −1 is due to the transverse optical (TO) mode of c-BN, while two absorption bands at 1400 and 770 cm −1 correspond to the h-BN phase and result from the in-plane B-N stretching mode and the out-of-plane B-N-B bending vibration, respectively [17]. It can be clearly observed that there is a continuous increase of the intensity of c-BN peak, while the positions of the c-BN peaks have no obvious shift with increased deposition time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1a shows the FTIR spectra obtained from BN films using pure N 2 plasma at 470 • C with different deposition times. The absorption band at 1091 cm −1 is due to the transverse optical (TO) mode of c-BN, while two absorption bands at 1400 and 770 cm −1 correspond to the h-BN phase and result from the in-plane B-N stretching mode and the out-of-plane B-N-B bending vibration, respectively [17]. It can be clearly observed that there is a continuous increase of the intensity of c-BN peak, while the positions of the c-BN peaks have no obvious shift with increased deposition time.…”
Section: Resultsmentioning
confidence: 99%
“…Such involvement of Ar ions may cause resputter of the deposited film, structural damage, and stress accumulation, especially under high ion energy conditions [15,16]. Although introducing H 2 into the working gases can effectively etch the sp 2 phase, leaving an sp 3 phase [17], the assistance of Ar for energetic ion bombardment is the major reason for the poor adhesion that is usually found, which severely hinders the application of c-BN films.…”
Section: Introductionmentioning
confidence: 99%
“…The complete peak assignment is also given in Table 1 . The volume fraction of the different BN phases of the bias-enhanced coating can be estimated by the relative intensities of the w -BN, c -BN and h -BN peaks using the following equation [ 39 , 40 ]. …”
Section: Resultsmentioning
confidence: 99%
“…[9] In order to carry out a good investigation on the initial growth of Ag films formation, the controllable preparation of samples is very important. The magnetron sputtering is an important technology for the films deposition [15][16][17][18][19][20] and an attractive alternative to prepare Ag films. [21][22][23][24][25] However, the common magnetron sputtering for the Ag films preparation is driven by the 13.56 MHz radio-frequency (RF) source.…”
Section: Introductionmentioning
confidence: 99%